Decision Support System for Selecting the Best Employee Using the Electre Method (Case Study: Maju Bersama Swalayan) - Tuti Andriani; Irpan Nainggolan; Arisman (Bahasa Indonesia, 2023)
Self-service employees come forward together who do not get an appreciation for the results that must be obtained will produce an increase and can produce growth from the company. Rewarding the best employees will increase morale and foster maximum levels of performance. Supporting criteria in decision making is the best step in selecting employees with the criteria applied to the system. The method of choosing the best with the best choice for the best employee selection. The highest aggregate value is obtained by the highest employee.